ANALISIS RASIO LAPORAN KEUANGAN PADA PT. SUMBER ALFARIA TRIJAYA TBK. TAHUN 2010 DAN 2011 - Rizqi, M Nur (STIE Binaniaga, 2013)
One means to determine the condition / financial performance of the company can be done by analyzing financial statements. Using the financial statements in the comparison include data on changes in the amount of dollars and percentages, then some financial ratios, such as liquidity ratios, solvency, activity and profitability will assist in analyzing and interpreting the financial position of a company As one of the strategic company in Indonesia, PT. Source Alfaria Trijaya Tbk which is engaged in the sale of everyday staples has the goal of becoming the leading retail food distribution network that can be owned by the public through a partnership (partnership), oriented to the empowerment of small entrepreneurs, fulfilling the needs and expectations of consumers, and be able to compete globally , Therefore, PT. Source Alfaria Trijaya Tbk is required to assess the condition and development of the company through the analysis of the ratio of the financial statements in order to PT. Source Alfaria Trijaya Tbk can maintain the existence of the company and is able to increase the growth of the company in the midst of an increasingly rapid economic growth and increasingly fierce competition. Based on the results of the discussion on the analysis of the ratio of the financial statements. Source Alfaria Trijaya Tbk in 2010 and 2011, the authors can draw conclusions as follows:1. From the liquidity factor in 2010 and in 2011 the company was said to be illiquid, as current assets less than its current debt. So here the company has been unable to fully meet its short term obligations on time2. From the solvability factors in 2010 and 2011, the company is still said to be solvable, since the total assets of sufficiently greater than the total debt, total assets in 2010 amounted to Rp. 4262929 (in millions of dollars), while total debts of Rp. 3177823 (in millions of dollars). While in 2011 the total assets of Rp. 5014932 (in millions of dollars) and total debt of Rp. 3554452 (in millions of dollars).3. From asset management factors (activity), the company showed good category, especially in the receivables turnover, which in 2010 resulted in turnover ratio of 60.03 times compared to the year 2011 only resulted in a ratio of 56.97 times. And also in asset turnover ratio shows the ratio of good results in 2010, amounting to 3.95 times compared with the year 2011 amounted to only 3.93 times.4. From the factor of profitability in 2010 and 2011, the company less well in generating profit, due under interest rate. Keyword:Rasio Analysis